Comparing the Effect of Photodynamic Therapy With 660 and 450 nm Lasers and Cold Atmospheric Plasma on Candida albicans: An Invitro Study: Effect of PDT and cold plasma on candida albicans - Azizi, Arash; Mousavi Zadeh, Seyedeh Elnaz; Shokouhi Mostafavi, Seyed Khalil; Vahedi, Mohammad (Journal of Lasers in Medical Sciences, 2025)
Introduction: The increasing occurrence of antifungal resistance agents poses a significant challenge in the field of dentistry, necessitating new therapeutic alternatives for treating fungal infections. This study compares the effect of photodynamic therapy (PDT) using two wavelengths of diode lasers and cold atmospheric plasma (CAP) on Candida albicans cultures. Methods: A standard 0.5 McFarland suspension of C. albicans was prepared and transferred to a 96-well microplate. These samples were divided into 10 groups as follows: 1- Positive control, 2- 450 nm laser, 3- PDT with 450 nm laser+curcumin, 4- 660 nm laser, 5- PDT with 660 nm laser+methylene blue, 6 and 7- Cold plasma for 180 and 210 seconds, 8- Nystatin, 9- Curcumin, 10- Methylene blue. Then the colony counts of C. albicans (CFU/mL) were recorded. Data analysis was performed using SPSS software, One way ANOVA, and Tamhane’s test (P<0.05). Results: The mean reduction in the number of C. albicans colonies in the nystatin group was significantly higher than all other groups (P<0.05). The 660 nm laser group showed significant reduction in the colony count compared to the positive control, 210-second cold plasma, and 450 nm PDT groups (P<0.05). The 180-second cold plasma group had significantly higher reduction in the colony count compared to the positive control and 450 nm PDT groups (P<0.05). The methylene blue, 450 nm laser, and 210-second cold plasma groups also showed significantly higher reductions compared to the positive control (P<0.05). Conclusion: Cold plasma with the feeding gas of helium for 180 seconds exposure and the lowpower 660 nm laser showed inhibitory effects on C. albicans colonies and were more effective than PDT. Nystatin application significantly reduced the number of C. albicans colonies and was more effective than cold plasma, laser irradiation, and PDT.